2019
DOI: 10.1007/s10864-019-09336-7
|View full text |Cite
|
Sign up to set email alerts
|

Headsprout Early Reading for Specific Literacy Difficulty: A Comparison Study

Abstract: This study compared the efficacy of the Headsprout © Early Reading (HER) program with SENCO-delivered supplementary literacy instruction. Participants were primary school children (aged 6-9) in receipt of free school meals and supplementary literacy instruction. Data were collected within their school setting. The treatment group received HER intervention, while the treatment as usual (TAU) group received SENCO-delivered intervention, inclusive of guided reading, paper-based phonics training and word recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
(24 reference statements)
1
7
0
Order By: Relevance
“…The HWOS group outperformed the other groups for the remaining two measures (LNF and PSF) as can be seen in Figure 2. Although findings in the current research are consistent with previous studies that support the use of Headsprout to improve reading skills (Huffstetter et al., 2010; Storey et al., 2017, 2020; Tyler et al., 2015; Watkins et al., 2016), the difference in gains across groups was not large enough to reach significance.…”
Section: Discussionsupporting
confidence: 83%
“…The HWOS group outperformed the other groups for the remaining two measures (LNF and PSF) as can be seen in Figure 2. Although findings in the current research are consistent with previous studies that support the use of Headsprout to improve reading skills (Huffstetter et al., 2010; Storey et al., 2017, 2020; Tyler et al., 2015; Watkins et al., 2016), the difference in gains across groups was not large enough to reach significance.…”
Section: Discussionsupporting
confidence: 83%
“…However, this study reported high levels of attrition that resulted in non‐equivalent groups, which weakens causal claim. A small RCT by Storey et al (2020) also reported large positive effects on reading skills for mainstream primary‐aged pupils at risk of reading failure. The remaining two small RCTs reported positive effects on reading with learners with intellectual disabilities (Ramdoss et al, 2020; Roberts‐Tyler et al, 2020).…”
Section: Resultsmentioning
confidence: 98%
“…We defined an outlier as a value below the first quartile minus three times the interquartile range (−1.24) or above the third quartile plus three times the interquartile range (2.07; Tukey, 1977). We identified one outlier at the upper end of the distribution (2.54; Storey et al, 2020) and winsorized the value to the upper fence value.…”
Section: Outlier Analysismentioning
confidence: 99%